2017
DOI: 10.1111/apm.12682
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic protein deimmunization by T‐cell epitope removal: antigen‐specific immune responses in vitro and in vivo

Abstract: Hirudin III is an effective anti-coagulant; however, in 40% of treated patients, a high-titer of anti-Hirudin III IgG antibodies is observed. Development of antibody responses requires the activation of helper T lymphocyte (HTL), which is dependent on peptide epitopes binding to HLA class II molecules. Based on computational prediction softwares, four new mutants of Hirudin III, T4K, S9G, V21G, and V21K, had been designed with the aim of reducing the binding affinity of these HTL epitopes. The constructed muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The identification of immunogenic epitopes in the protein structure by computational tools has been a strategy used to achieve a reduction in the immunogenicity of several proteins [78][79][80]. It is also the case of ASNase from E. coli, where the use of bioinformatics techniques has allowed engineering the enzyme with the aim of obtaining an improved therapeutic agent [58,81,82].…”
Section: Resultsmentioning
confidence: 99%
“…The identification of immunogenic epitopes in the protein structure by computational tools has been a strategy used to achieve a reduction in the immunogenicity of several proteins [78][79][80]. It is also the case of ASNase from E. coli, where the use of bioinformatics techniques has allowed engineering the enzyme with the aim of obtaining an improved therapeutic agent [58,81,82].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported different strategies to generate amino acid substitutions for the purpose of reducing immunogenicity (for recent studies see refs ). In several studies, alanine replacements have been used (see refs ).…”
Section: Resultsmentioning
confidence: 99%
“…Other de‐immunization studies also based on introducing single amino acid substitutions into known epitopes have been reported in the literature (see, for example, refs , as cited above). In those studies, mild and conservative substitution strategies, such as ‘alanine scans’, were shown to be effective.…”
Section: Discussionmentioning
confidence: 99%